PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PEMBIBITAN TANAMAN KAKAO ( Theobroma cacao L. ) DI POLYBAG. - Nora, Maida; Amir, Nurbaiti; Aminah, R. Iin Siti (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
Effect of Media Composition Against Plant Nursery Cocoa (Theobroma cacao L.) in Polybag. This study aims to determine the effect of media composition in the appropriate planting cocoa plant nurseries (Theobroma cacao L.) In Polybag . The research was conducted dilahan experimental garden campus of University of Muhammadiyah Palembang C Semambu Island Village District of North Inderalaya Ogan Ilir South Sumatra Province. This study will take place from the month of May to July 2015. This study used a method of execution that is Rancanga Randomized (RAK) are arranged singly with 5 treatments and 5 replications. Each treatment consisted of 4 plants example. The treatment in the study include M0 = Soil Topsoil (control), M1 = 1: 1: 1 (Land: Chicken Manure: Rice Husk), M2 = 1: 2: 1 (Land: Chicken Manure: Rice Husk), M3 = 1: 1: 2 (Soil: Chicken Manure: Rice Husk), M4 = 2: 1: 1 (Land: Chicken Manure: Rice Husk ). The parameters observed in this study was the increase of plant height (cm), in the number of leaves (pieces), root fresh weight (g), root dry weight (g), berangkaasan wet weight (g), beragkasan dry weight (g), Results of analysis of variance showed that the composition ratio of the planting medium does not influence significantly on all the observed variables.